Equidad de Género y Biodiversidad - Madden, Lidiethe (2007)
This paper analizes the efforts made to contribuye the environment protection since a gender and biodiversity perspectiva, regaining the central practices of food security healthy production and forests conservation. Through a brief retelling, it identifies the main international events, agreements, conventions among others thaf Costa Rica has agreed upon in terms of human sustainable development, it also recognizes the main contributions frum Eco feminist females theoreticians. It also propose some recommendations focused on a culture of respect, equality of opportunities and environmental conservation.